Digital-based critical success factors in the Italian hospitality business - Del Chiappa, Giacomo; Rashidin , Salamun (Piccola Impresa / Small Business, 2024)
Purpose: Small and medium enterprises (SMEs) are the backbone of the economies of many countries around the world. In recent years, the debate around the digital transformation of the European tourism industry has gained huge attention from both academia and industry. Approach: Despite their importance, there is still a dearth of research devoted to analysing the digital-based critical success factors (DCSFs) for the successful operation of small-scale hotel businesses and comparing them with those of larger hotels. This study aims to deepen the scientific debate around this somewhat overlooked research area by presenting and discussing the results of an empirical study conducted on a sample of 367 Italian hotel businesses. Finding: Results of exploratory factor analysis indicate that the main DCSFs are "internet and social media", "virtual reality", "robots,", and "artificial intelligence in data analytics". Moreover, a series of ANOVA independent t-tests reveals that significant differences exist in the hotel managers' and owners' views about DCSFs based on the hotel size (SMEs versus large hotels) and their level of education and work experience. Implications: Contributions to the current body of knowledge and managerial implications are discussed, and suggestions for further research are derived.